Didactic Principles of Teaching Musical Literacy Through Music Culture Classes. - Alimjon Tursunov (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
Tuning is usually achieved when singing vocal-choir exercises, and performance techniques specific to the song being sung are used in it. The resulting tuning is achieved in the performance ensemble in the first instrument, and based on this experience, learning and artistic performance of the song becomes easier. The article describes the didactic principles of teaching musical literacy through music culture lessons.